2017
DOI: 10.18632/oncotarget.15705
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral kynurenine/tryptophan ratio is not a reliable marker of systemic indoleamine 2,3-dioxygenase: A lesson drawn from patients on hemodialysis

Abstract: Indoleamine 2,3-dioxygenase (IDO) has emerged as a pivotal enzyme for mediating immune tolerance. Because IDO metabolizes tryptophan into kynurenine, the plasma kynurenine/tryptophan (Kyn/Trp) ratio has been widely used as a marker of systemic IDO. Here, we evaluated the clinical value of using the plasma Kyn/Trp ratio to estimate cell-mediated immune responses to tuberculin skin testing and risk of new bacterial infection. We also compared the Kyn/Trp ratio to a novel IDO marker, the IDO median fluorescence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…An increase in the ratio in alcohol-dependent subjects, 8 weeks after withdrawal, does not correlate with neopterin, 14 a marker of IDO induction, as IFN-γ also induces the key enzyme of neopterin synthesis, GTP cyclohydrolase I. In a study 15 . That the increase in the ratio in this study was independent of IDO activity is further suggested by the failure of these PBMCs to metabolise Trp to Kyn.…”
Section: Does the Plasma [Kyn]/[trp] Ratio Always Reflect Ido Activity?mentioning
confidence: 86%
See 2 more Smart Citations
“…An increase in the ratio in alcohol-dependent subjects, 8 weeks after withdrawal, does not correlate with neopterin, 14 a marker of IDO induction, as IFN-γ also induces the key enzyme of neopterin synthesis, GTP cyclohydrolase I. In a study 15 . That the increase in the ratio in this study was independent of IDO activity is further suggested by the failure of these PBMCs to metabolise Trp to Kyn.…”
Section: Does the Plasma [Kyn]/[trp] Ratio Always Reflect Ido Activity?mentioning
confidence: 86%
“…An increase in the ratio in alcohol-dependent subjects, 8 weeks after withdrawal, does not correlate with neopterin, 14 a marker of IDO induction, as IFN-γ also induces the key enzyme of neopterin synthesis, GTP cyclohydrolase I. In a study 15 of patients with haemodialysis from 2 separate centres, the significant increase in the plasma [Kyn]/[Trp] ratio caused by a significant increase in [Kyn] and a significant decrease in [Trp], does not correlate with IDO activity measured directly in peripheral blood mononuclear cells (PBMCs). That the increase in the ratio in this study was independent of IDO activity is further suggested by the failure of these PBMCs to metabolise Trp to Kyn.…”
Section: Does the Plasma [Kyn]/[trp] Ratio Always Reflect Ido Activity?mentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, it was shown that peripheral KTR is influenced by various factors and is not a reliable marker of IDO activity [16,46]. KTR is reliable for measurement of IDO activity in isolated cells or cell cultures of cells capable of producing functional IDO, e.g., in endothelial cells, antigen-presenting cells, fibroblasts, macrophages, and dendritic cells [10,46]. In plasma, IDO-independent loss of TRP (enhancing KTR) may be caused by decreased dietary intake of TRP or due to the action of liver TDO increase for instance in renal diseases [43].…”
Section: Discussionmentioning
confidence: 99%
“…IDO1 expression is known to induce the suppression of effector T cells, promoting T reg activation and tolerance. Recently, IDO1 activity has been identified as a potential clinical marker of bacterial infection in hemodialysis patients [41], linking dysregulation of the immune system to hemodialysis chronic microinflammation and risk of infection. Experimental data support the hypothesis that IDO1 suppresses innate and adaptive immune responses, confirming its relevance to promote chronic inflammatory syndromes [42].…”
Section: Discussionmentioning
confidence: 99%